The influence of L1 Tibetan and L2 Chinese on Tibetan university students' L3 English listening and speaking: an exploratory analysis - Weber, J (2024)
This study explores the phenomenon of crosslinguistic influence (CLI) in third language acquisition (L3A), specifically focusing on phonological transfer to L3 English by L1 Tibetan-L2 Mandarin bilinguals in China. Despite the growing body of research on L3A, phonological transfer remains an underexplored area, particularly in the context of non-Indo-European languages such as Tibetan. The study therefore investigates the impact of L1 Tibetan and L2 Mandarin on the acquisition of three L3 English phonemes (/v/, /f/, and /k/) by 34 Tibetan speakers, using a combination of production and perception tasks to compare the trilingual group’s accuracy on these three phonemes with that of a control group of 34 monolingual English speakers in order to determine sources of crosslinguistic influence. It also examines whether a relationship between phonological production and perception in L3 English exists. The study is guided by three research questions that are addressed through the lens of the five most currently prominent L3A models: L2 Status Factor hypothesis (L2SF), Cumulative Enhancement Model (CEM), Typological Primacy Model (TPM), Scalpel Model, and Linguistic Proximity Model (LPM), in addition to the lens of privileged L1 transfer. The Scalpel Model best predicted the results, but the study did not find conclusive evidence that any model can fully explain L3 phonological acquisition. However, the findings did contribute insights into the complex interplay between phonological production and perception in multilingual learners, and the study also underscores the need for further research in underrepresented linguistic contexts to develop more comprehensive models of L3A that hold true across linguistic domains.